2014
DOI: 10.1111/jawr.12240
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐Development Groundwater Conditions Surrounding Memphis, Tennessee: Controversy and Unexpected Outcomes

Abstract: Reliance on groundwater resources by differing governing bodies can create transboundary disputes raising questions of ownership and apportionment as the resource becomes strained through overuse or threatened by contamination. Transboundary disputes exist at varying scales, from conflicts between countries to smaller disputes between intrastate jurisdictions. In 2005 within the United States, the State of Mississippi filed a lawsuit against its political neighbor and their utility, the City of Memphis and Mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…The previous studies support a general conceptual model for groundwater flow in the Memphis area in which, prior to development, groundwater recharged into the Memphis aquifer in the hilly exposure belt of the Memphis Sand, 40 to 120 km southeast of the city of Memphis (Brahana and Broshears 2001). Groundwater flow was southeast to northwest toward the city of Memphis and supported flowing, artesian well conditions during the early years of water production from the aquifer in the late 1800's (Waldron and Larsen 2014). This groundwater is relatively old, with residence times ranging from about 1,000 to 3,000 years old based on 14 C data (data in Graham and Parks 1986).…”
Section: Journal Of Contemporary Water Research and Education Ucowrmentioning
confidence: 97%
See 2 more Smart Citations
“…The previous studies support a general conceptual model for groundwater flow in the Memphis area in which, prior to development, groundwater recharged into the Memphis aquifer in the hilly exposure belt of the Memphis Sand, 40 to 120 km southeast of the city of Memphis (Brahana and Broshears 2001). Groundwater flow was southeast to northwest toward the city of Memphis and supported flowing, artesian well conditions during the early years of water production from the aquifer in the late 1800's (Waldron and Larsen 2014). This groundwater is relatively old, with residence times ranging from about 1,000 to 3,000 years old based on 14 C data (data in Graham and Parks 1986).…”
Section: Journal Of Contemporary Water Research and Education Ucowrmentioning
confidence: 97%
“…The Flour Island Formation forms the lower confining layer for the Memphis aquifer and upper confining unit for the Fort Pillow aquifer, another water resource for the region. Waldron and Larsen (2014) used historical water level data to reconstruct the predevelopment (prior to 1906) water table and potentiometric surface for the Memphis aquifer. Early studies suggested that the primary source of recharge to the Memphis aquifer was infiltration in upland regions, east and southeast of Memphis (Hosman et al 1968), including the southeastern part of Shelby County (Criner et al 1964).…”
Section: Journal Of Contemporary Water Research and Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Commonly, it is recognized that urbanization decreases groundwater recharge due to higher imperviousness (Foster et al. ; Hutchinson and Woodside ; WMO ; Waldron and Larsen ). However, the effect of urbanization on groundwater systems is not always very clear, as it depends on the geological and hydrogeological setting, and the adopted stormwater management practices.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this impact is relevant, as it may affect the baseflow in urban streams and rivers (Paul and Meyer 2001;Rose and Peters 2001;Burns et al 2005;Schoonover et al 2006;Lan-Anh et al 2012;Bhaskar et al 2016a). Commonly, it is recognized that urbanization decreases groundwater recharge due to higher imperviousness (Foster et al 1994;Hutchinson and Woodside 2002;WMO 2008;Waldron and Larsen 2015). However, the effect of urbanization on groundwater systems is not always very clear, as it depends on the geological and hydrogeological setting, and the adopted stormwater management practices.…”
Section: Introductionmentioning
confidence: 99%